Experiencing STEM at the Lab School: Situated Histories and Enacted Pedagogies - Jagger, Susan; Trifonas, Peter Pericles (Encounters in Theory and History of Education / Rencontres en Théorie et Histoire de l'Éducation / Encuentros en Teoría e Historia de la Educación, 2025)
This paper examines how the historical, theoretical, and lived commitments of John Dewey’s progressive education are enacted in contemporary STEM learning at the University of Chicago Laboratory Schools. Placing STEM within the sociopolitical and environmental transformations of late nineteenth-century Chicago, we link Dewey’s philosophies to the engineering and civic challenges that shaped the city. Drawing on classroom observations, teacher conversations, and composite vignettes, we show how STEM learning in a grade one class foregrounds student-driven inquiry in community and place. Three themes characterize these experiences: experience and exploration through ongoing encounters with Wooded Island; problem solving and place via collaborative design challenges connected to Chicago’s built environment; and ethics and relationships as students consider their responsibilities toward more-than-human community members. The authors argue that these practices exemplify a transdisciplinary STEM that is historically grounded, ecologically situated, and democratically oriented. As Chicago again undertakes place-making with the Obama Presidential Center, Deweyan principles continue to offer a living curriculum that invites young learners to make meaning, act together, and imagine more just and sustainable futures.